Cerium Chloride Catalyzed, 2‐Iodoxybenzoic Acid Mediated Oxidative Dehydrogenation of Multiple Heterocycles at Room Temperature. Issue 9 (8th March 2017) - Hati, Santanu; Sen, Subhabrata
Abstract : Catalytic cerium chloride was found to activate 2‐iodoxybenzoic acid (IBX) for the oxidative dehydrogenation of tetrahydroisoquinolines, tetrahydro‐β‐carbolines, and thiazolidines to their dehydrogenated and aromatic forms at room temperature in moderate to excellent yields. The robustness of the protocol was demonstrated by scaling up the reactions to multigram quantities. Abstract : Anhydrous cerium chloride is a suitable catalyst to improve the oxidizing ability of 2‐iodoxybenzoic acid (IBX) towards the oxidative dehydrogenation of heterocycles at room temperature.